2006
DOI: 10.1007/s10620-006-9116-2
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for an Involvement of the P38 and JNK Mitogen-Activated Protein in Inflammatory Bowel Diseases

Abstract: Involvement of mitogen-activated protein (MAPK) in inflammatory bowel disease (IBD) remains enigmatic. We sought to evaluate the expression and activity of p38 and JNK MAPK in IBD and 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis; and the effects of a p38 inhibitor, SB203580, in TNBS colitis. P38 and JNK were quantified in colonic mucosa of 28 IBD patients and 19 controls and in 77 TNBS or control mice treated or not with SB203580. Colitis severity was assessed by survival, macroscopic and microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…We and others (19,21) have shown an upregulation of the MAPK pathway in response to TNBS instillation. Nevertheless, the role of p38 in IBD remains controversial, because its pharmacological inhibition had no effect in colitic mice (42). In the present study, we have shown that an ALA-rich formula is able to inhibit activation of NF-kB, a key transcriptional factor in the gut that regulates the inflammatory response and oxidative stress.…”
Section: Discussionmentioning
confidence: 60%
“…We and others (19,21) have shown an upregulation of the MAPK pathway in response to TNBS instillation. Nevertheless, the role of p38 in IBD remains controversial, because its pharmacological inhibition had no effect in colitic mice (42). In the present study, we have shown that an ALA-rich formula is able to inhibit activation of NF-kB, a key transcriptional factor in the gut that regulates the inflammatory response and oxidative stress.…”
Section: Discussionmentioning
confidence: 60%
“…Previous study showed that the JNK inhibitor, SP600125, partially reduced DSS-induced wasting and colonic mucosal ulceration in mice [30], whereas another study indicated the lack of a role for JNK in IBD pathogenesis [35]. Therefore, the precise role of JNK activation in the pathogenesis of colitis is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be mentioned that several studies performed in mice or in tandem with human material have failed to definitively link p38 activity or expression with IBD [64,65]. These studies can possibly be reconciled with the other contradictory data as being due to different experimental set-ups.…”
Section: Therapeutic Relevance Of Map Kinase Inhibitors?mentioning
confidence: 99%